Faktor-Faktor Yang Ada Hubungan Dengan Tuli Sensorineural Pada Penderita Yang Berobat Di Poli THT-KL RSUD Labuang Baji Makassar - Tompo, Anindya Khaerunnisa; Hasbullah, Ayu Ameliyah; Hariadi, Anisyah (Bosowa Medical Journal, 2025)
Hearing Loss or Deafness is the partial or total inability to hear sound in one or both ears. Hearing loss can be divided based on the type of deafness which includes conduction deafness, sensorineural deafness and mixed deafness. Sensorineural Hearing Loss (SNHL) is a disorder of the sensor system where the problem is located in the inner ear, especially in the cochlea or nerve from the inner ear to the brain. This type of deafness is usually permanent. Medical therapy and surgery cannot cure sensorineural deafness completely. The use of hearing aids can help. This study aimed to determine the risk factors for sensorineural deafness such as hypertension, nutritional status, smoking history, use of ototoxic drugs and noise exposure. This study was conducted on 52 patients with a ratio of 1: 1 in the case and control groups who sought treatment at the ENT Poly Labuang Baji Hospital Makassar. This study uses an observational analytic method with a Case-Control research design using primary data by measuring Blood Pressure using a Tensimeter, Weight using a Body Weight Scale, Height using a Microtoise and Interviews using a Questionnaire to find out the history of smoking, the use of ototoxic drugs and noise exposure in patients who seek treatment at the ENT Poli Labuang Baji Hospital Makassar. Based on the univariate and bivariate data analysis results using the chi-square test by paying attention to the P-Value and Odds Ratio (OR) on each variable. The results of statistical analysis are hypertension (P-value 0.026), nutritional status (P-value 0.006), smoking history (P-value 0.021), use of ototoxic drugs (P-value 0.079) and noise exposure (P-value 0.026). The conclusion of the research on Factors that have a relationship with Sensorineural Deafness in Patients who seek treatment at the ENT Poli Labuang Baji Hospital Makassar obtained a significant relationship between hypertension, nutritional status, smoking history and noise exposure and a non-meaningful relationship in the use of ototoxic drugs against patients with sensorineural deafness who seek treatment at the ENT Poli Labuang Baji Hospital Makassar.